Social and executive functioning in individuals with autism spectrum disorder without intellectual disability: The case–control study protocol of the CNeSA study - Donno, Federica; Balia, Carla; Boi, Jessica; Manchia, Mirko; Zuddas, Alessandro; Carucci, Sara (Frontiers in Child and Adolescent Psychiatry, 2023)
Several studies suggest that children and adolescents with Autism Spectrum Disorder (ASD) often present deficits in Executive Functions (EF). The research on cold EF shows a high heterogeneity across different cohorts of patients as well as different study designs, while studies investigating hot EF and their relationship with different ASD phenotypes are still limited and related only to specific domains, although this concept could contribute to clarify the phenotypical variability by explaining the difficulties encountered by ASD individuals in daily life, where stimuli are often emotionally charged. With the aim to identify specific neuropsychological profiles in children and adolescents with ASD without Intellectual Disability (ID), we designed a study protocol comparing a clinical sample of ASD subjects to aged-matched (10-17 y) Typically Developing Controls (TDC) on a neuropsychological test battery investigating both “cold” and “hot” EF with the purpose of further investigating their relationships with ASD symptoms. Autonomic measures including heart rate, heart rate variability, skin conductance and salivary cortisol were also recorded before/during/after the neuropsychological testing session. This paper describes the case-control study protocol named “Caratterizzazione NEuropsicologica del disturbo dello Spettro Autistico, senza Disabilità Intellettiva, CNeSA study”, its rationale, the specific outcome measures, and their implications for the clinical management of ASD subjects and a precision medicine approach.